Kazakh Language as Spoken in China: Problems and Research Perspectives - Tazhibayeva, S.Zh.; Nevskaya, I.A.; Mutali, A.K.; Kadyskyzy, A. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
The status of Kazakh has greatly changed after gaining its sovereignty. It became the state language of the Republic of Kazakhstan. Kazakhstan is now a country with a consiquent language policy, and good international relations in the fields of economy, policy, culture. Kazakh is spoken not only in Kazakhstan but also far beyond its borders. The largest group of ethnic Kazakhs outside Kazakhstan resides in China. The Kazakh language in the People’s Republic of China (PRC) has the status of a minority language. In the era of globalization in the 21st century, one of the most important language issues around the world is the threat of extinction of the world’s minority languages. In this respect, it is important to study the sociolinguistic situation of the Kazakh language as a minority language. The main reasons for the endangerment of languages are technological, social, cultural, economic and political trends of globalization. One of the topical issues of Kazakhstani sociolinguistics is research on different varieties of Kazakh outside the country